Kepemimpinan Bermutu: Konsep Pengembangan Lembaga Pendidikan Islam - Chairunnisa, Ema; Najiyah, Choirotun; Salsabila, Hajar; Cendekia Dikara, Wanadya Nirmalasari (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2020)
The development of Islamic educational institutions in Indonesia seems increasingly complex in the current era. The management model requires a more modern order and relevant to the development of the times to be able to compete with other public institutions. Islamic educational institutions are often underestimated. Therefore, the concept of quality leadership is something that is important in advancing the management of Islamic education. The need for quality leadership that is able to manage various aspects, allows the achievement of the objectives of the institution to the fullest. This research will describe some important aspects of quality leadership in the management of Islamic educational institutions. This article uses the literature review method, which means collecting various writings, whether in the form of articles, journals, books, and in accordance with the theme to be discussed.Â